2019
DOI: 10.1177/1559325818819946
|View full text |Cite
|
Sign up to set email alerts
|

Lower Body Acceleration and Muscular Responses to Rotational and Vertical Whole-Body Vibration at Different Frequencies and Amplitudes

Abstract: Aim:The aim of this study was to characterize acceleration transmission and neuromuscular responses to rotational vibration (RV) and vertical vibration (VV) at different frequencies and amplitudes.Methods:Twelve healthy males completed 2 experimental trials (RV vs VV) during which vibration was delivered during either squatting (30°; RV vs VV) or standing (RV only) with 20, 25, and 30 Hz, at 1.5 and 3.0 mm peak-to-peak amplitude. Vibration-induced accelerations were assessed with triaxial accelerometers mounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In particular frequency, amplitude and movement principle were found to be very heterogeneous between the included studies (see Tables 2 and 3). Since the effects of WBV and RVE are strongly dependent upon the parameters that characterize mechanical vibration, such as the frequency and amplitude of the vibration as well as the duration of vibration exposure 27,64 the results are described in qualitative terms, and they are intrinsically associated with a significant degree of uncertainty. Overall, the analysis stresses the need for further research on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…In particular frequency, amplitude and movement principle were found to be very heterogeneous between the included studies (see Tables 2 and 3). Since the effects of WBV and RVE are strongly dependent upon the parameters that characterize mechanical vibration, such as the frequency and amplitude of the vibration as well as the duration of vibration exposure 27,64 the results are described in qualitative terms, and they are intrinsically associated with a significant degree of uncertainty. Overall, the analysis stresses the need for further research on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…This greater muscle activation generated by rotational WBV can result in increased isometric activity of the musculature [ 54 ]. Likewise, it has been shown that accelerations in the ankle are greater during rotational WBV [ 55 , 56 ]. This greater mechanical load on the ankle produced with rotational WBV can further activate the musculature at this level, especially the anterior tibial, whose neural excitability is highly associated with mediolateral oscillation [ 57 ] and gastrocnemius [ 53 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of 30 participants, 15 were randomly assigned to the WBVe group receiving a single session of WBVe via a vibrating platform (Galileo ® Med S; Novotec Medical, Pforzheim, Germany) with a vibration frequency of 20 Hz and amplitude of 4 mm while keeping a half-squat position on the platform. We used rotational vibration to follow the report of Zaidell et al [ 16 ], which suggested that rotational vibration may be a safe platform to minimized head vibration and more suitable for subjects who cannot keep balance in the squatting position. The control group participated in the same session with the same posture without the application of vibration.…”
Section: Methodsmentioning
confidence: 99%